Adaptive Resistance of Staphylococcus aureus to Cefquinome Sulfate in an In Vitro Pharmacokinetic Model with Transcriptomic Insights - Yue Hu; Hao Zhu; Xingbo Zhang; Yuhui Wu; Jingtao Li; Nan Li; Zhanbo Cai; Yuhui Yang (Microorganisms)
Cefquinome sulfate has a strong killing effect against Staphylococcus aureus (S. aureus), but bacterial resistance has become increasingly widespread. Experiments were conducted to investigate the pattern of adaptive resistance of S. aureus to cefquinome sulfate under different dosage regimens by using pharmacokinetic-pharmacodynamics (PK-PD) modeling, and the adaptive-resistant bacteria in different states were screened and subjected to transcriptomic sequencing. The results showed that the minimum inhibitory concentration of Staphylococcus aureus under the action of cefquinome sulfate was 0.5 μg/mL, the anti-mutation concentration was 1.6 μg/mL, and the mutation selection window range was 0.5~1.6 μg/mL. In the in vitro pharmacokinetic model to simulate different dosing regimens in the animal body, there are certain rules for the emergence of adaptive drug-resistant bacteria: the intensity of bacterial resistance gradually increased with culture time, and the order of emergence was tolerant bacteria (TO) followed by persistent bacteria (PE) and finally resistant bacteria (RE). The sequence reflected the evolution of adaptive drug resistance. Transcriptome Gene Ontology (GO) analysis revealed that differentially expressed genes were involved in cellular respiration, energy derivation by oxidation of organic compounds, and oxidation–reduction processes. The differentially expressed genes identified functioned in the synthesis of cell membranes, cytoplasm, and intracellular parts. A Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis found that 65 genes were differentially expressed after cefquinome sulfate treatment, of which 35 genes were significantly upregulated and 30 genes were significantly downregulated. Five genes, sdhB, sdhA, pdhA, lpdA, and sucC, may be involved in network regulation. This study revealed the cross-regulation of multiple metabolic pathway networks and the targets of network regulation of S. aureus to produce adaptive drug resistance. The results will provide guidance for clinical drug use in animals infected with S. aureus.